PENGARUH PEMBERIAN JUS KUBIS MERAH (Brassica oleracea var. capitata L) TERHADAP KADAR GLUKOSA DARAH PADA TIKUS PUTIH (Rattus norvegicus) DIABETES MELITUS - Zulkarnaen, Ratu Bella Cyantika; Mulyo, Gurid Pramintarto Eko; Judiono, Judiono; Isdiany, Nitta; Hastuti, Widi; Purba, Jedya Lucas A. (Jurnal Gizi dan Dietetik, 2024)
Diabetes mellitus is a disease that threatens global health which is characterized by increased blood glucose levels. Natural treatment is needed to maintain stable blood glucose levels in diabetes mellitus sufferers. Red cabbage (Brassica oleracea var. capitata L) is a vegetable that contains quite high levels of antioxidants and can be used to lower blood glucose levels. This study aims to determine the effect of giving red cabbage juice on blood glucose levels in white rat with diabetes mellitus. The research design was a true experimental laboratory with a pre and post test control group. A sample of 24 male white rats was divided into 4 groups, namely negative control group (K-), positive control group (K+), treatment group 1 (P1), and treatment group 2 (P2). Data analysis used the Dependent t test and the Kruskal-Wallis test with the Mann-Whitney test with a significance level of p<0.05. The results of the Dependent t test showed the effect of the intervention on the four groups (p<0.05). The results of the Kruskal-Wallis test showed that the four groups were different (p<0.05). The results of the Mann-Whitney test showed significant differences in each group comparison (p<0.05). Giving red cabbage juice at a dose of 1.8 gr/200 grBW and a dose of 3.6 gr/200 gBW for 14 days had an effect on blood glucose levels when rats were induced by 45 mg/kgBW of streptozotocin. It is hoped that there will be further research regarding the effect of giving red cabbage juice on fasting blood glucose levels in humans with diabetes mellitus and further research using flavonoids from red cabbage extract.